Informing Immersed Citizens: The Impact of Interactivity on Comprehending News in Immersive Journalism - Hannah Greber; Loes Aaldering; Sophie Lecheler (Media and Communication)
Immersive journalism has emerged as an innovative journalistic approach promising enhanced attention and understanding through interactive, virtual environments. Previously, this was mostly tested through factual knowledge. However, evaluating immersive audio-visual modalities solely along factual knowledge falls short of considering, firstly, what about and how an immersive experience is remembered and, secondly, the importance of considering the perceptions surrounding information acquisition. Therefore, this study examines how interactivity in immersive journalism affects traditional as well as novel ways of comprehending news, such as episodic memory. In addition, we consider perceptions related to knowledge. We draw on a laboratory experiment (N = 149) testing the effect of three levels of interactivity provided (no interactivity vs. looking around vs. looking around + control over pace and order of storyline). Results indicate that a higher range of interactivity does not influence factual memory, but leads to an increase in perceived knowledge, thus indicating an illusion of knowledge. Moreover, there is a tendency to formulate more subjective takeaways in the high-interactivity condition, while interactivity did not influence the credibility evaluations. This provides partial empirical support for the credibility paradox of immersive journalism.